1999
DOI: 10.1515/bc.1999.008
|View full text |Cite
|
Sign up to set email alerts
|

Not More than Three Tissue Kallikreins Identified from Organs of the Guinea Pig

Abstract: The large and varied multigene families of tissue kallikreins of rat and mouse are considered to selectively release as many bioactive peptides. In order to determine whether a similar family of enzymes is expressed in the organs of the guinea pig purification studies were performed. Tissue kallikreins from the submandibular gland, coagulating gland/prostate complex and the pancreas were separated by affinity chromatography on benzamidine-Sepharose. Amino-terminal sequences, the patterns of hydrolysis rates of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 46 publications
(72 reference statements)
0
3
0
Order By: Relevance
“…No more than three tissue kallikreins were identified from organs of the guinea pig [27]. Southern blot analysis detected KLK2 and KLK3 positive bands in several nonhuman primate species including macaque, orangutan, chimpanzee and gorilla but not cows and rabbits [28].…”
Section: Kallikreins In Other Speciesmentioning
confidence: 99%
“…No more than three tissue kallikreins were identified from organs of the guinea pig [27]. Southern blot analysis detected KLK2 and KLK3 positive bands in several nonhuman primate species including macaque, orangutan, chimpanzee and gorilla but not cows and rabbits [28].…”
Section: Kallikreins In Other Speciesmentioning
confidence: 99%
“…Previous efforts focused on the evolutionary history of KLKs focused in the characterization of the mouse [14], [15], rat [16], [17] and pig genes [18], as well as of individual members in mastomys [19], cynomolgus monkey [20], rhesus monkey [21], [22], dog [23], guinea pig [24], macaque orangutan, chimpanzee, gorilla [25], cat [26], horse and cow [17], [22] and cotton-top tamarin [27]. Elliot et al [28] had performed the first Bayesian phylogenetic analysis and suggested the origin of the KLK family before the marsupial-placental split (approximately 125–175 million years ago, mya).…”
Section: Introductionmentioning
confidence: 99%
“…The guinea-pig pregnancy shares several structural similarities with the human gestation, regarding the trophoblastic interstitial and vascular invasion and the haemomonochorial placenta [22-24]. Moreover, the guinea-pig has been postulated as an ideal model to study the role of the tissue kallikrein-kinin system [25,26]. …”
Section: Introductionmentioning
confidence: 99%